2006
DOI: 10.1002/app.22344
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficient of DMSO in polyacrylonitrile fiber formation

Abstract: ABSTRACT:A H 2 O/dimethyl sulfoxide(DMSO) mixture was used as the coagulation bath for the wet-spun process of acrylonitrile/ammonium itaconate copolymers fibers. Diffusion coefficient of DMSO in the protofibers prepared by acrylonitrile/ammonium itaconate copolymers was determined. It has been found that diffusion coefficient of DMSO outflow of the protofibers prepared by acrylonitrile/ammonium itaconate copolymers synthesized by the solution polymerization is highest compared with those of acrylonitrile/ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…28,37−39 Fitting of eq 4 allows us to obtain the different values of a within acceptable deviations as provided in Table 2 for all polymer systems investigated so far. 5,30,40 The values are in line with the available literature values for other polymer systems 34,35,41,42 in dilute and semidilute systems, with the former reflected as such in good models for polymer systems developed by Wisńiewska et al 5,29 for PEG/PEO-water. As before with PDMS-ethyl acetate systems, the obtained data for a remain applicable for all of these polymer systems of all different molecular weights.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…28,37−39 Fitting of eq 4 allows us to obtain the different values of a within acceptable deviations as provided in Table 2 for all polymer systems investigated so far. 5,30,40 The values are in line with the available literature values for other polymer systems 34,35,41,42 in dilute and semidilute systems, with the former reflected as such in good models for polymer systems developed by Wisńiewska et al 5,29 for PEG/PEO-water. As before with PDMS-ethyl acetate systems, the obtained data for a remain applicable for all of these polymer systems of all different molecular weights.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…Increased dope temperatures are normally used, ranging from 70 to 100 °C . Heating affects the dope viscosity and therefore its ease of spinning .…”
Section: Preparation Of Polymer Solutionmentioning
confidence: 99%
“…In addition to the aforementioned differences between the spinning methods, the properties of the precursor fibers are also influenced by the fabrication of the spinning dope and the spinning processes. Some important factors that have been studied include spinning dope, spinning parameters and conditions, and additions . First, with respect to the spinning dope, Hou et al studied the influence of H 2 O/DMSO mixture suspension polymerization, aqueous suspension polymerization, and DMSO solution polymerization on the phase separation of PAN fibers under the same coagulation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the fibers obtained through aqueous solution polymerization have gentler exchange behavior between solvent and non‐solvent and higher crystallinity. Yin et al also demonstrated that aqueous suspension polymerization can be used to obtain fibers with round cross‐sections. By increasing the solid content of the copolymer in the dope, the diffusion between solvent and non‐solvent can be mitigated in the coagulation bath.…”
Section: Introductionmentioning
confidence: 99%